Plasmon polaritons in 1D Cantor-like fractal photonic superlattices containing a left-handed material (2011)
ABSTRACT: The propagation of light incident upon a 1D photonic superlattice consisting of successive stacking of alternate layers of a right-handed nondispersive material and a metamaterial, arranged to form a Cantor-like fractal, is considered. Plasmon-polariton excitations are thoroughly investigated within the transfer-matrix approach and shown to strongly depend on the Cantor step number N. More specifically, the number of plasmon-polariton bands corresponds to the number 2N −1 of metamaterial layers within the unit cell.